2020
DOI: 10.3390/molecules25030506
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Impairs the Survival of Triple Negative Breast Cancer Cells: Cellular and Molecular Analyses

Abstract: Triple negative breast cancer (TNBC) is an aggressive breast cancer subtype. Non-available targeted therapy for TNBC represents its biggest treatment challenge. Thus, finding new promising effective drugs is urgently needed. In the present study, we investigated how berberine, a natural isoquinoline, impairs the survival of TNBC cells in both cellular and molecular levels. Our experimental model was based on the use of eight TNBC cell lines: MDA-MB-468, MDA-MB-231, HCC70, HCC38, HCC1937, HCC1143, BT-20, and BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In this context, the implementation of a complementary treatment might find the solution, as naturally derived compounds offer a great deal of anti-cancer activity. Natural compounds like curcumin, quercetin, berberine, etc have been shown to inhibit TNBC proliferation and aggressiveness (Kundur et al, 2019;El Khalki et al, 2020). In the present manuscript, we investigated the potential of 15,16-dihydrotanshinone-I (DHTS) for its anti-migratory action in TNBC cell lines.…”
Section: Dihydrotanshinone-i Modulates Epithelial Mesenchymal Transition (Emt) Thereby Impairing Migration and Clonogenicity Of Triple Nementioning
confidence: 99%
“…In this context, the implementation of a complementary treatment might find the solution, as naturally derived compounds offer a great deal of anti-cancer activity. Natural compounds like curcumin, quercetin, berberine, etc have been shown to inhibit TNBC proliferation and aggressiveness (Kundur et al, 2019;El Khalki et al, 2020). In the present manuscript, we investigated the potential of 15,16-dihydrotanshinone-I (DHTS) for its anti-migratory action in TNBC cell lines.…”
Section: Dihydrotanshinone-i Modulates Epithelial Mesenchymal Transition (Emt) Thereby Impairing Migration and Clonogenicity Of Triple Nementioning
confidence: 99%
“…Berberine was cytotoxic against all treated TNBC cell lines such as MDA-MB-231, MDA-MB-468, HCC1937, HCC70, HCC38, BT-20, HCC1143, and BT-549. Among all these experimented cell lines, the most sensitive ones were HCC70 (IC 50 = 0.19 µM), BT-20 (IC 50 = 0.23 µM), and MDA-MB-468 (IC 50 = 0.48 µM) [ 45 ]. Using flow cytometry techniques, BBR at 0.5 and 1 µM for 120 and 144 h not only induced cell cycle arrest at first growth (G1) and second-growth (G2)/medium phases, but it also triggered significant apoptosis [ 45 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Meeran et al have showed that BBR treatment-induced apoptosis through the alteration of mitochondrial membrane potential and the cleavage of caspase-3, caspase-9 protein, and PARP in PC-3 prostate cancer cells [ 110 ]. BBR significantly induces apoptosis in MDA-MB-468, HCC70, and BT-20 triple-negative breast cancer cells through the cleavage of caspase-7 and caspase-8 protein in MDA-MB-468 and BT-20 cell line, and by the cleavage of PARP in HCC70 cells [ 111 ]. In addition, Wen et al have reported that the combination of BBR and tamoxifen (TAM) induced cell cycle arrest in the G1 phase and apoptosis through the induction of p21Cip-1 and the increase of the Bax/Bcl-2 ratio in MCF7 and tamoxifen-resistant MCF7/TAMR breast cancer cells [ 112 ].…”
Section: Berberine and Cancermentioning
confidence: 99%